Some (p,q)-integral Inequalities - Genç Türk, İlker (Sarajevo Journal of Mathematics, 2025)
In this paper, we obtain a (p,q)-analogue of an open problem represented by Q. A. Ngo et al. in the paper, Notes on an integral inequality, J. Inequal. Pure and Appl. Math., 7(4) (2006), Art. 120, by using analytic and elementary methods in (p,q)-calculus.